Traffic Monitoring and Analysis Second International Workshop, TMA 2010, Zurich, Switzerland, April 7, 2010.Proceedings - Ricciato, Fabio; Mellia, Marco; Biersack, Ernst; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the Second International Workshop on Traffic Monitoring and Analysis, TMA 2010, held in Zurich, Switzerland, on April 7, 2010 - colocated with PAM 2010, the 11th Passive and Active Measurement conference. The workshop is an initiative from the COST Action IC0703 "Data Traffic Monitoring and Analysis: Theory, Techniques, Tools and Applications for the Future Networks". The 14 papers contained in this volume were carefully reviewed and selected from 34 submissions. They encompass research areas related to traffic analysis and classification, measurements, topology, discovery, detection of specific applications and events, packet inspection, and traffic inference. The papers are organized in topical sections on analysis of internet datasets, tools for traffic analysis and monitoring, traffic classification, and performance measurements.
Analysis of Internet Datasets -- Understanding and Preparing for DNS Evolution -- Characterizing Traffic Flows Originating from Large-Scale Video Sharing Services -- Mixing Biases: Structural Changes in the AS Topology Evolution -- Tools for Traffic Analysis and Monitoring -- EmPath: Tool to Emulate Packet Transfer Characteristics in IP Network -- A Database of Anomalous Traffic for Assessing Profile Based IDS -- Collection and Exploration of Large Data Monitoring Sets Using Bitmap Databases -- DeSRTO: An Effective Algorithm for SRTO Detection in TCP Connections -- Traffic Classification -- Uncovering Relations between Traffic Classifiers and Anomaly Detectors via Graph Theory -- Kiss to Abacus: A Comparison of P2P-TV Traffic Classifiers -- TCP Traffic Classification Using Markov Models -- K-Dimensional Trees for Continuous Traffic Classification -- Performance Measurements -- Validation and Improvement of the Lossy Difference Aggregator to Measure Packet Delays -- End-to-End Available Bandwidth Estimation Tools, An Experimental Comparison -- On the Use of TCP Passive Measurements for Anomaly Detection: A Case Study from an Operational 3G Network.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Information storage and retrieval systems; Information systems; Information Systems; Computer Science; Computer Communication Networks; System Performance and Evaluation; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Management of Computing and Information Systems